PENGARUH HARGA, CITRA MEREK DAN LABEL HALAL TERHADAP MINAT BELI KONSUMEN LIPSTIK WARDAH DI KABUPATEN BANYUWANGI - Almar'atus Sholihah; Lusiana Ulfa Hardinawati; Lilis Yuliati (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
The study is to know determine and analyze the effect of price, brand image and halal label on consumer interest buying Wardah lipstick product in the Banyuwangi. Population in this study used people in the Banyuwangi Regency area, who used Wardah lipstick product. In this study used 100 respondents who used Wardah lipstick in Banyuwangi Regency area. The methode used multiple linear regression analysis. The result of this research is: a) Price has a positive and significant influence on consumer buying interest in Wardah lipstick products in Banyuwangi. Banyuwangi Regency. b) Brand image has a positive and significant influence on consumer buying interest in Wardah lipstick products in the Banyuwangi Regency area. c) Halal label has a positive and significant effect on consumer buying interest in Wardah lipstick products in the Banyuwangi Regency area.